Regularities in Evaporation and Carryover of Polydisperse Water Flow Droplets During Motion Through High-Temperature Gases; Chemical and Petroleum Engineering; Vol. 51, iss. 7-8 - Kuznetsov G. V. Geny Vladimirovich (2015, 2015)
Title screen